If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y + 1 = 2y + -26 Reorder the terms: 1 + 8y = 2y + -26 Reorder the terms: 1 + 8y = -26 + 2y Solving 1 + 8y = -26 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 1 + 8y + -2y = -26 + 2y + -2y Combine like terms: 8y + -2y = 6y 1 + 6y = -26 + 2y + -2y Combine like terms: 2y + -2y = 0 1 + 6y = -26 + 0 1 + 6y = -26 Add '-1' to each side of the equation. 1 + -1 + 6y = -26 + -1 Combine like terms: 1 + -1 = 0 0 + 6y = -26 + -1 6y = -26 + -1 Combine like terms: -26 + -1 = -27 6y = -27 Divide each side by '6'. y = -4.5 Simplifying y = -4.5
| .5f+10=48 | | 6(2x+3)+2= | | (16x-3)(2)=0 | | 8p+9p=34 | | a-6-7a=1-6a | | 11c-4-3=8 | | (16x-3)(8)=0 | | 1/3x-1/6y=1 | | -4/5a=12/17 | | 2x-6=8-2x | | 3=2y | | 16x+3=47 | | 4+17/-2=0 | | 8(2a-8)=-4(-3a+6) | | 2c+c+12=14 | | 1/2f+10=48 | | 33/d=12 | | z/14=-28 | | 1-2x=-9+8x | | 8x+4x+2=12x+2 | | 87=(2x+7) | | x^2+3x+14=47.75 | | (15)t+(9)=15t+9 | | d/12=33 | | -20=7 | | 5-5n=-55 | | 8a+10a= | | 16/1/4=x | | 32-(-86)= | | 5x+8-1x=20+4x-12 | | 12d=33 | | x^2-14x-27=0 |